Expanding Catch and Release DNA Decoy (CRDD) Technology with Pyrimidine Mimics. Issue 58 (25th August 2022) - Kennelly, Samantha A.; Moorthy, Ramkumar; Otero, Ruben Silva; Harki, Daniel A.
Abstract: Catch and release DNA decoys (CRDDs) utilize photochemically responsive nucleoside analogues that generate abasic sites upon exposure to light. Herein, we describe the synthesis and evaluation of four candidate CRDD monomers containing nucleobases that mimic endogenous pyrimidines: 2‐nitroimidazole (2‐NI ), 2‐nitrobenzene (2‐NB ), 2‐nitropyrrole (2‐NP ) and 3‐nitropyrrole (3‐NP ). Our studies reveal that 2‐NI and 2‐NP can function as CRDDs, whereas 3‐NP and 2‐NB undergo decomposition and transformation to a higher‐ordered structure upon photolysis, respectively. When incorporated into DNA, 2‐NP undergoes rapid photochemical cleavage of the anomeric bond (1.8 min half‐life) to yield an abasic site. Finally, we find that all four pyrimidine mimics show significantly greater stability when base‐paired against the previously reported 7‐nitroindole CRDD monomer. Our work marks the expansion of CRDD technology to both purine and pyrimidine scaffolds. Abstract : Expanding the chemical toolbox : The toolbox of catch and release DNA decoys (CRDDs) has been expanded to pyrimidine mimics. CRDD technology uses photolysis to form abasic sites in DNA. This work shows that a 2‐nitropyrrole (2‐NP ) pyrimidine mimic undergoes rapid photochemical cleavage of the anomeric bond to yield an abasic site at a rate comparable to that of the previously reported 7‐nitroindole (7‐NI ) purine mimic.